Reaching teens : strength-based communication strategies to build resilience and support healthy adolescent development. 35.3, Raising independent children who will choose to be interdependent with us. Ginsburg. - Ginsburg, Kenneth R.; American Academy of Pediatrics (Elk Grove Village, Ill. : American Academy of Pediatrics, 2014)
This instructional video, from the "Reaching Teens: Strength-Based Communication Strategies to Build Resilience and Support Healthy Adolescent Development" series produced by the American Academy of Pediatrics, is a lecture by adolescent medicine specialist Kenneth R. Ginsburg about raising children to be both independent and interdependent with parents.
Title from resource description page (viewed August 03, 2017).
Speaker: Kenneth R. Ginsburg.
In English.
Keywords: Child rearing; Autonomy in adolescence; Youth development -- United States; Parent and child; Child Rearing; Parent-Child Relations; Éducation des enfants; Autonomie chez l'adolescent.; Jeunesse -- Développement -- États-Unis.; Parents et enfants; Autonomy in adolescence; Child rearing; Parent and child; Youth development; United States; Educational films; Film excerpts; Film excerpts; Educational films; Films éducatifs.